PENGARUH SISTEM PENGENDALIAN INTERNAL, BUDAYA TRI HITA KARANA PADA KINERJA PEMERINTAH - I Wayan Gde Yogiswara Darma Putra; Ni Made Vita Indriyani (WICAKSANA: Jurnal Lingkungan dan Pembangunan, 2020)
This study aims to obtain empirical evidence of the influence of internal control systems, Tri Hita Karana Culture on government performance. The analytical tool used is multiple linear regression. The population in this study is the Regional Device Organization (OPD) in the Badung District Government as many as 35 OPD. The sample was chosen using nonprobability sampling method with saturated sample technique. With the respondent of Regional Administration Organization Financial Administration Officer (PPK-OPD) consisting of one head of field / secretary / sub-district head, head of planning sub-section, and head of sub-finance section so that the number of respondents is 105 respondents. The results show that the internal control system has a positive effect on government performance. Tri Hita Karana culture has a positive effect on government performance